Technology contributions in the construction of an inclusive education: the work with a disabled visual student in Math classes - Santos, Flávio Lopes dos; Cordeiro, Janivaldo Pacheco; Gonçalves, Nahun Thiaghor Lippaus Pires; Thiengo, Edmar Reis (Educação Matemática Debate, 2017)
This article discusses the reality of a low vision student in a state school of Espírito Santo during the math classes, works the matrices content through technology as a pedagogical resource and also articulates theoretical basis of Vygotsky, Leontiev, Galperin and Papert. The reports and statements described point out the reality of an inclusive classroom, considering the student and the didactic model of discipline. The results point out the limitations related to the resources and technologies available in key points for the relevance of the teaching-learning process and the suggestion for the use of the Google Drive service as a didactic resource, which aims to contribute to the improvement of actions and conditions in face of the specific needs of the student and of the notes.